Discover the future of sustainable rest (Ingeniería, Sostenibilidad y Sociedad, 2023)
The present article introduces the range of mattresses made from recycled materials, emphasizing their comfort and their contribution to environmental conservation. The benefits of sustainable rest, such as waste reduction and support for the circular economy, are highlighted. The availability of personalized options and the importance of eco-certifications are mentioned. Furthermore, the commitment of brands to sustainability is emphasized, along with the significance of educating and raising awareness about eco-friendly mattresses.
Keywords: ecological mattresses; recycled materials; sustainability; care for the environment; sustainable rest; comfort